Obverse and reverse: the monetary image of Aelia Eudoxia, Empress of the East (395-404) - Furlani, João Carlos (Romanitas - Revista de Estudos Grecolatinos, 2017)
Too many representations of certain characters are conceived and conditioned almost exclusively by information presented in written documents, be they contrary or in favor of who is portrayed. In the case of Eudoxia, empress of the East between 395 and 404, it is no different. Documents of a textual nature, largely Christian, disqualify the empress, as well as being guilty of attacking and conspiring against John Chrysostom during the events that led the bishop to the exile. However, material documentation allows us to visualize a distinct representation of that propagated by written documents. Therefore, our purpose in this article is to analyze the image and numismatic representation of Aelia Eudoxia conveyed through a set of coins minted in her honor during the Arcadius government, taking into consideration that a rich discussion about the struggle of representations about Eudoxia can be developed, since the symbols of the monetary artifacts express meanings and intentions that go against what is presented until then about the empress, while at the same time demonstrating different possibilities of feminine performance in Late Antiquity.